Effects of Adrenergic Agonists and Antagonists on Cardiopulmonary Function During Normobaric Hypoxia in Rat - Bölter, Christian; Gabriel, Philipp; Appelt, Peter; Salameh, Aida; Schierle, Katrin; Rassler, Beate (Frontiers in Physiology, 2019)
Pulmonary edema (PE) is an issue widely noted in acute exposure to hypoxia as seen in high altitude climbers, yet the etiology of this is not defined. Previous studies in rats showed that both hypoxia and strong sympathetic activation may induce PE. As acute exposure to hypoxia is accompanied by sympathetic activation, we assume that this may impair pulmonary circulation and contribute to the development of hypoxic PE. The aim of the present study was to investigate the effects of adrenergic agonists and antagonists as models for overstimulation and suppression, respectively, of sympathetic activity on cardiovascular function and formation of PE in hypoxic rats. Norepinephrine or adrenergic blockers were infused to rats exposed to normobaric hypoxia with 10% O2 over time intervals up to 24h. Normoxic and hypoxic controls received 0.9% NaCl infusion. We evaluated hemodynamic function and lung histology. A significant decrease of left ventricular systolic function was observed after 6h of hypoxia. This effect was less pronounced with -adrenergic blockade but was more severe with combined - plus -adrenergic blockade. Norepinephrine delayed the onset of hypoxic left ventricular depression but did not reduce its degree. Significant PE developed after 16h of hypoxia. It regressed under - but not with -adrenergic blockade, and was aggravated by combining hypoxia with norepinephrine. Almost half of the animals exposed to hypoxia over 16 to 24 h suffered cardiorespiratory arrest during the experiment and presented with signs of acute right ventricular failure. They had significantly elevated serum catecholamine concentrations and significantly stronger PE than the others. Notably, most of them had received norepinephrine or combined adrenergic blockade. Mild changes in serum catecholamine concentrations indicated that hypoxic sympathoadrenergic activation was only weak. Hence, it was not sufficient to prevent left ventricular depression. However, the results show that -adrenergic mechanisms contribute to the formation of hypoxic PE. Adrenergic blockade but also sympathetic overactivity may induce pulmonary congestion, PE and acute right ventricular failure indicating that a fine balance of sympathetic activation under hypoxic conditions is crucial. This has important implications for climbers to high altitude as well as for patients suffering from hypoxia.